The value relevance of accounting variables towards market stock price across the industries in Malaysia / Dk Noor Aziantie Ag Sobudin - Ag Sobudin, Dk Noor Aziantie (2016)
Earnings per share and book value per share are the summary of accounting variables in financial statement which widely used in business community in order to track financial performance and at the same time provided necessary information for investors as indicators for decision making in choosing stock. Both of the essential components of finance accounting and reporting has been used to indicate the market stock price by adopting Ohlson Theory model which the previous research done usually cover on its relevant over years. However, some of the previous research done did not comparing the usefulness of earnings and book value across the different industries. Thus, the objective of this paper is to identify the relevancy value of earnings per share and book value per share towards the market stock price across the different industries in Malaysia. Panel Data approach were used in this paper and from the findings shows that earnings per share and book value per share have significant relationship with the market stock price across the different industries in Malaysia. Consumer products industry has the highest explanatory power for earnings per share while plantations industry has the highest explanatory power for book value per share.